Surge in Capital Inflows, Response of the Government, and Effects on the Economy: The Philippine Case - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 1995)
The Philippine economy has manifested signs of recovery due to various factors such as political and economic stabilization. Hence, inflows are expected to continue in the future. While these capital flows are positive developments, it carries with it adverse impacts on the real sector of the economy. This paper analyzes the pattern of capital flows and the government's response to these surges. The effects of these policy responses in the real sectors are also investigated.
Keywords: 330; real exchange rate; nontradable commodities; inflows; remittances; external balances; capital outflows; foreign investment